Interstitial fluid transport in linea alba is involved in acupuncture-induced attenuation of ovarian hypofunction in aged rats - Yaoyao Zhu; Ge Lu; Weixin Li; Chenchen Su; Pengfei Du; Shuyou Wang; Li Yang; Huanfang Xu; Yigong Fang; Xiaojing Song (Frontiers in Endocrinology)
BackgroundAge-related ovarian dysfunction, characterized by declining follicular reserve and hormonal imbalance, poses a significant challenge in reproductive endocrinology, severely compromising fertility and quality of life. Although acupuncture at conception vessel acupoints is an effective therapeutic approach for managing ovarian dysfunction, the biological underpinnings bridging peripheral stimulation to systemic endocrine regulation remain elusive. Emerging evidence has highlighted interstitial fluid (ISF) dynamics as a potential mediator of mechanotransduction. However, it remains to be elucidated whether ISF transport in the linea alba (abdominal trajectory of conception vessel) influences ovarian function, and whether acupuncture at conception vessel acupoints exerts its therapeutic effects through ISF-mediated substance transport along the linea alba.MethodsWe used fluorescence imaging to observe ISF migration patterns in the linea alba of rats, where conception vessel acupoints are located. In addition, we investigated the ovarian functional changes post-ISF obstruction and evaluated the therapeutic effects of acupuncture on ovarian dysfunction in aged rats, both in unblocked and ISF-blockade conditions.ResultsFluorescence imaging revealed ISF transport along the linea alba, with tracers migrating linearly, a pattern abolished by surgical blockade. Abnormal ISF transport in the linea alba may affect the homeostasis of reproductive hormone levels. Serum follicle-stimulating and luteinizing hormones increased while E2 decreased, accompanied by follicular depletion and hypothalamic-pituitary-ovarian axis dysregulation. Acupuncture at CV4 attenuated ovarian aging, elevating developmental follicle counts, reducing granulosa cell apoptosis, and restoring hypothalamic-pituitary-ovarian axis function. Crucially, these therapeutic benefits were nullified under ISF blockade conditions.ConclusionOur results suggest that ISF transport in the linea alba may serve as an important mechanistic pathway bridging acupuncture stimulation to ovarian regulation. Our study not only provides a mechanistic basis for the clinical efficacy of acupuncture in treating ovarian disorders but also identifies ISF dynamics as a novel therapeutic target in age-related ovarian dysfunction.